Profil Soal Numerasi yang Dikembangkan oleh Calon Guru Matematika - Hardiyanti, Yulia Tria; Fachrudin, Achmad Dhany; Widadah, Soffil (MATHEdunesa, 2024)
Prospective teachers are at the forefront in forming quality students. As a prospective teacher, it is good to be able to master the material given to students, including prospective teacher’s mastery of numeracy questions. For this reason, this research aims to determine the numeracy abilities of prospective teachers in applying problems in everyday life. This qualitative descriptive research uses numeracy questions created by students by providing a sample of 27 students. The technical analysis used is manual analysis by two analysts and Cohen Kappa analysts agreed that the quality of the questions being developed was still at the lowest level. Apart from that, grouping numeracy questions based on cognitive level, context, and domain content. Furthermore, the Cohen Kappa analysis shows a value of 1, which means there has been good agreement between the two analysts.